My Guardian: a personal safety mobile application - Raja Azman, Raja Feninferina; Qistina Suraya; Abdul Rahim, Fiza; Mohd Azmi, Muhammad Sufyian; Mohd Ariffin, Noor Afiza (IEEE, 2018)
Smartphones have become somewhat essential and most people have one on hand at all times. Smartphones have been considered a blessing as it has many capabilities and is not just limited to calling and text messaging unlike the regular mobile phone. It can be utilised by converting it into an emergency safety device that can be used when users are placed in a potentially unsafe and dangerous situation. It will ease the process of getting help by allowing users to quickly notify people of an emergency situation with a press of a button. My Guardian, a personal safety application developed for smartphones, intends to help allow users to notify a set of predefined contacts when they feel they are in an unsafe situation or is simply nervous about travelling alone. With a press of a button, the application will send a text message to these contacts with their location coordinates and a personalized emergency alert message.